Eastern Orthodoxy in the processes of the post-communist political transformations - Viktor Yelenskyі (Політичні дослідження, 2021)
It is a sort of truism in the social sciences that since the late 1970s the world has been witnessing the great return of religion into global politics and international relations. Paradigm shift in theorists’ concepts and practitioners’ perception of previously underestimated dimension were tremendously influenced by the chain of events signaled the new role of religion in politics, and among them by the explosive religious revival in countries where the Eastern Orthodoxy was the majority religion which started even well before the collapse of the USSR and Yugoslavia.Eastern Orthodoxy is the major religious denomination in 12 European countries, all but two of which (Greece and Cyprus) are former communist states. In this perspective , reasoning over Orthodoxy’s destiny is to greater extent reasoning over the post-communist political development as a phenomenon.Article proves that Eastern Orthodoxy provided post-communist states with symbolism and common ideological ground for both leftists and rightists, former communists and former dissenters, and extended a symbolic framework to the so-called Soviet people who lost the sense of belonging and were searching for their new identity. Orthodox Churches that saw itself and were widely perceived as the historic repository of nationhood, national values, and, quite often, as the savior of a nation's very existence, suggested itself as a main actor in the process of new identity building. Orthodoxy became the primary vehicle for the awakening of collective identity for the groups surrounded by or competed with groups of different religions. This trend was very clear in some of the episodes which marked the first post-communist decade. Conflicts in the former Yugoslavia, the northern Caucasus and Transcaucasia were given a strong religious emphasis and religion was rapidly turned into the factor of political and national mobilization. At the same time, the aspiration of the newly independent states to gain the independence of their churches from Moscow and Belgrade has created an additional powerful geopolitical source of tension. While the process of bestowing Autocephaly to the Orthodox Church in Ukraine that met with fierce resistance from the Russian state, showed how far Russia could go to maintain ecclesiastical control over Ukraine. And also, what is the role of Orthodoxy as a symbolic and institutional resource in contemporary political processes.